The AO trauma CPP bone infection registry: Epidemiology and outcomes of Staphylococcus aureus bone infection. Issue 1 (27th July 2020) - Morgenstern, Mario; Erichsen, Christoph; Militz, Matthias; Xie, Zhao; Peng, Jiachen; Stannard, James; Metsemakers, Willem‐Jan; Schaefer, Dirk; Alt, Volker; Søballe, Kjeld; Nerlich, Michael; Buckley, Richard E.; et al.
Abstract: Bone infection represents a serious complication of orthopedic surgery and Staphylococcus aureus is the most common pathogen. To improve the understanding of host‐pathogen interaction, we developed a biospecimen registry ( AO Trauma CPP Bone Infection Registry ) to collect clinical data, bacterial isolates, and serum from patients with S. aureus bone infection. A prospective multinational registry with a 12‐month follow‐up was created to include adult patients (18 years or older) with culture‐confirmed S. aureus infection in long bones after fracture fixation or arthroplasty. Baseline patient attributes and details on infections and treatments were recorded. Blood and serum samples were obtained at baseline, 6, and 12 months. Patient‐reported outcomes were collected at 1, 6, and 12 months. Clinical outcomes were recorded. Two hundred and ninety‐two patients with fracture‐related infection (n = 157, 53.8%), prosthetic joint infection (n = 86, 29.5%), and osteomyelitis (n = 49, 16.8%) were enrolled. Methicillin‐resistant S. aureus was detected in 82 patients (28.4%), with the highest proportion found among patients from North American sites (n = 39, 48.8%) and the lowest from Central European sites (n = 18, 12.2%). Patient outcomes improved at 6 and 12 months in comparison to baseline. The SF‐36 physical component summary mean (95% confidence interval) score, however, did not reach 50 at 12 months. The cure rate at the end of the study period was 62.1%. Although patients improved with treatment, less than two‐thirds were cured in 1 year. At 12‐month follow‐up, patient‐reported outcome scores were worse for patients with methicillin‐resistant S. aureus infections.